Optimized design of the power consumption test of mountain orchard transporters - Li, Jiaxue; Zhong, Muyuan; Zhang, Yanlin; Bao, Xiulan; Li, Shanjun; Liu, Mingdi; Wang, Linghao (International Journal of Agricultural and Biological Engineering, 2021)
In order to study the influence rule of various factors on the operation power consumption of the traction orchard transporter and realize the optimal design of the operation power consumption of the transporter, according to the traditional experience and the existing research foundation, the monorail transporter test bench was designed and built on the basis of the whole structure and operation characteristics of the transporter. Taking the motor frequency, track gradient and load as the investigation factors, and the driving shaft power, shaft power transmission and mechanical efficiency as the evaluation indices, the orthogonal test was conducted, and the range analysis of the influence effect was carried out according to the test results. The primary and secondary orders of the influence of various factors were obtained that motor frequency was greater than track gradient and track gradient was greater than load. According to the orthogonal test results, the second-order response surface method was used to establish the optimization model of the power consumption of the transporter, and the model was verified on the test bench. The results showed that the relative error between the model optimization value and the test value based on the response surface power optimization model was less than 10%, which indicated that the power optimization model had satisfactory performance. The research can provide a reference for the orchard conveyor to choose the parameter combination which can save power consumption and the motor that matches power consumption.Keywords: mountain orchard transporter, power consumption, orthogonal test, optimization model, analysisDOI: 10.25165/j.ijabe.20211405.6209Citation: Li J X, Zhong M Y, Zhang Y L, Bao X L, Li S J, Liu M D, et al. Optimized design of the power consumption test of mountain orchard transporters. Int J Agric & Biol Eng, 2021; 14(5): 107–114.